New COVID protocol for elite athletes to returning to sport - Horvath, Z.; Nagy, D. (2021 14th International Congress on Image and Signal Processing, BioMedical Engineering and Informatics (CISP-BMEI), 2018)
The COVID-Sars19 virus was a big problem in sports too. Before the Olympics, lots of Athletes lost motivation and the infected athletes lost some time from the preparation or missed the last qualification chance. The most important question how can we reduce the recovery time after the infection what is safety, without any cardiac risk. In our research, we create one new protocol that can reduce this time and the athletes don't lose too much time and don't lose their performance.